Attitudes Toward Gender-Based Violence Among Sexually Active Adult Men at High Risk for HIV in Rustenburg, South Africa. Issue 3 (June 2022) - Makkan, Heeran; Maenetje, Pholo; Chetty-Makkan, Candice M.; Muchiri, Evans; Latka, Mary H.; Edward, Vinodh A.; Price, Matt A.; Omosa-Manyonyi, Gloria; Lindan, Christina
Gender-based violence (GBV) toward women is widespread and has been associated with increased HIV risk. We investigated attitudes toward GBV among men living in Rustenburg, South Africa, who were enrolled in a longitudinal HIV incidence study. Participants were 18 to 49 years old, reported high risk sexual activity in the last 3 months, and were HIV-uninfected. Attitudes toward GBV were evaluated using responses to a five-item standardized questionnaire about men perpetrating physical violence on a female spouse; responses to each item were scaled from 1 ( no agreement ) to 4 ( strong agreement ) and summed. Total scores >10 were considered permissive toward GBV. Among the 535 men analyzed, nearly half ( N = 229, 42.8%) had a GBV score >10. Being young (18–24 years) (adjusted odds ratio [aOR] = 1.53, 95% confidence interval [CI] [1.06, 2.22]), having less years of education (aOR = 1.61, 95% CI [1.11, 2.32]), and reporting no current sexual partner at baseline (aOR = 2.10, 95% CI [1.06, 4.14]) were independently associated with permissive attitudes toward GBV. The following behaviors reported in the last 3 months were also associated with high GBV scores: having a new female partner (aOR = 1.78, 95% CI [1.02, 3.10]), and having had an STI (aOR = 1.85, 95% CI [1.15, 2.99]). Consuming alcohol prior to sex in the last month (aOR = 1.59, 95% CI [1.09, 2.31]) was also associated with high GBV scores. A large proportion of South African HIV-uninfected men in this analysis reported permissive attitudes toward GBV. These attitudes were associated with HIV risk behavior. Integrating GBV and HIV prevention programs is essential.